An in vitro experiment on the interaction of charcoal or wheat bran with 11-nor-9-carboxy-Δ9-tetrahydrocannabinol and its glucuronide - Skopp, Gisela; Mikus, Gerd (Analytical and bioanalytical chemistry, 2013)
The rather long yet variable terminal half-lives and detection times since last use of urinary cannabinoids may partly be attributed to their enterohepatic circulation which generally can be interrupted or restricted by chemical adsorbents. Therefore, an in vitro experiment was performed to study the adsorption/binding of 11-nor-9-carboxy-Δ9-tetrahydrocannabinol (THC-COOH) and its glucuronide to activated charcoal and wheat bran; remaining concentrations were determined by liquid chromatography/tandem mass spectrometry. Adsorption/binding of 1,000 ng/mL of free or conjugated THC-COOH was complete using as little as 5 mg of charcoal whereas adsorption/binding to wheat bran increased with increasing amounts. Taking of remedies affecting enterohepatic recycling of THC-COOH and its glucuronide may challenge interpretation of cannabinoid concentrations used to detect or assess frequency of drug use or the time since last drug consumption.
Published online: 29 September 2013
Im Titel ist "9" bei delta (als griechisches Symbol) hochgestellt
Gesehen am 03.02.2022